Can Social Health Insurance Be Successfully Introduced and Expanded in Papua New Guinea? - World Bank Group (World Bank, Washington, DC, 2015)
Cross-country comparisons have identified several enabling conditions required to ensure the sustainability of payroll tax-based systems. These are: (i) a large formal labour market; (ii) a growing economy; (iii) an administrative capacity for collection; and (iv) good regulatory and oversight structures. Political willingness is another important factor. The brief below discusses in detail the technical enabling conditions in the context to introduce and expand social health insurance in Papua New Guinea (PNG). Successful introduction of social health insurance (SHI) financing in PNG will, in part, depend on the feasibility of expanding coverage to the entire population, including the informal sector. A second important factor is how an increase in contribution rates will affect labour and capital markets. Expanding SHI coverage to the informal sector will be challenging in almost all contexts. The population in the formal sector is relatively easy to enrol and collect contributions from due to the availability of employment earnings records. The population in the informal sector is typically not affiliated with any organisation from which to enrol and collect premiums. They are also poorer and less able to afford premiums.